2002
DOI: 10.1086/345288
|View full text |Cite
|
Sign up to set email alerts
|

Gamma-Ray Bursts, Supernova Kicks, and Gravitational Radiation

Abstract: We suggest that the collapsing core of a massive rotating star may fragment to produce two or more compact objects. Their coalescence under gravitational radiation gives the resulting black hole or neutron star a significant kick velocity, which may explain those observed in pulsars. A gamma-ray burst can result only when this kick is small. Thus only a small fraction of core-collapse supernovae produce gamma-ray bursts. The burst may be delayed significantly (hoursdays) after the supernova, as suggested by re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
77
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 71 publications
(77 citation statements)
references
References 32 publications
0
77
0
Order By: Relevance
“…; see Rampp et al 1998) have been neglected, but they suggest that gravitational wave emission from massive collapses may be much less important than from compact binary mergers. On the other hand, recent semianalytical estimates (Fryer, Holz, & Hughes 2002;Davies et al 2002;van Putten 2001) have indicated that instabilities in the collapsing core or in the accretion disk of a collapsar GRB could lead to significantly stronger gravitational wave signals than expected from the previous numerical estimates. It is therefore of interest to reexamine the gravitational wave signals expected from various specific GRB progenitors that have been recently discussed and based on current astrophysical models to consider the range of rates and strains expected in each case, for comparison with the LIGO sensitivity.…”
Section: Introductionmentioning
confidence: 83%
See 2 more Smart Citations
“…; see Rampp et al 1998) have been neglected, but they suggest that gravitational wave emission from massive collapses may be much less important than from compact binary mergers. On the other hand, recent semianalytical estimates (Fryer, Holz, & Hughes 2002;Davies et al 2002;van Putten 2001) have indicated that instabilities in the collapsing core or in the accretion disk of a collapsar GRB could lead to significantly stronger gravitational wave signals than expected from the previous numerical estimates. It is therefore of interest to reexamine the gravitational wave signals expected from various specific GRB progenitors that have been recently discussed and based on current astrophysical models to consider the range of rates and strains expected in each case, for comparison with the LIGO sensitivity.…”
Section: Introductionmentioning
confidence: 83%
“…The high rotation rate is required to form a centrifugally supported disk around a central, possibly spinning black hole, to power a GRB jet. A high rotation rate, however, may be conducive to the development of bar or fragmentation instabilities in the collapsing core or/and in the massive disk around the central object (Nakamura & Fukugita 1989;Bonnell & Pringle 1995;van Putten 2001van Putten , 2002Davies et al 2002;Fryer et al 2002). The asymmetrically infalling matter also perturbs the black hole's geometry, which leads to ringdown gravitational radiation.…”
Section: Emission Mechanismsmentioning
confidence: 99%
See 1 more Smart Citation
“…A related suggestion relies on the coales-cence of proto-NS binary as providing the kick (Davies et al 2002). The biggest uncertainty for such scenarios is that it is not clear core fragmentation can take place in the collapse (and numerical simulations seem to say no; see Fryer & Warren 2003).…”
Section: Other Possibilitiesmentioning
confidence: 99%
“…The violent formation of black holes has long been proposed as a potential source of gravitational waves. Therefore, we have reason to expect strong association between GRBs and gravitational waves [3][4][5]. In this paper, we report on a search for a possible short burst of gravitational waves associated with GRB030329 using data collected by the Laser Interferometer Gravitational-Wave Observatory (LIGO).…”
Section: Introductionmentioning
confidence: 99%